Immediate Early Proto-Oncoproteins and Membranes: Not Just An Innocent Liaison - A. Borioli, Graciela (Current Protein and Peptide Science, 2011)
Proto-oncoproteins are a heterogeneous group of proteins that induce cellular differentiation, proliferation and growth, acting at different points of signaling cascades and in different cell compartments, through many different mechanisms. If the proto-oncogenes that give raise to proto-oncoproteins undergo genetic damage, they become oncogenes and their products are the oncoproteins responsible for cellular transformation in cancer. Some proto-oncoproteins are related to membranes and they exert their function at this level. Among these are receptors and receptor-like growth factors, membrane associated tyrosine kinases, and small GTPases. Other proto-oncoproteins are transcription factors and as such, their best known functional context is promoter DNA regions. Consequently, DNA is widely viewed as their most relevant non protein partner. Any interaction of these proteins with membranes is generally overlooked and, when considered, the membrane is regarded as a reservoir for timely release requiring proteolytic activity. However, this status quo should be revised. Some Immediate-Early proteins that are mobilized in the cell shortly after stimulus are also a subset of the transcription factor kind of proto-oncoproteins. These particular Immediate-Early proto- Oncoproteins (IEOs) exceed strict DNA related functions. Gathering evidence coming from biophysical studies on one hand and from molecular and cellular studies on the other hand, converge suggesting a link between them and membranes. In this review we discuss the conception that transcription factors with the features of IEOs exert their function in cellular processes, not only through association to DNA related to targeted transcription, but also through association to membranes related to global replication and transcription.
Keywords: Fra-1